2017
DOI: 10.1038/srep45541
|View full text |Cite
|
Sign up to set email alerts
|

Unacylated ghrelin promotes adipogenesis in rodent bone marrow via ghrelin O-acyl transferase and GHS-R1a activity: evidence for target cell-induced acylation

Abstract: Despite being unable to activate the cognate ghrelin receptor (GHS-R), unacylated ghrelin (UAG) possesses a unique activity spectrum that includes promoting bone marrow adipogenesis. Since a receptor mediating this action has not been identified, we re-appraised the potential interaction of UAG with GHS-R in the regulation of bone marrow adiposity. Surprisingly, the adipogenic effects of intra-bone marrow (ibm)-infused acylated ghrelin (AG) and UAG were abolished in male GHS-R-null mice. Gas chromatography sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 51 publications
3
53
0
Order By: Relevance
“…On the other hand, unacylated‐ghrelin does not share the protective effect of acyl‐ghrelin in a mouse model of PD . Intriguingly, the post‐translational acylation of ghrelin by the enzyme, ghrelin‐O‐acyl transferase, may provide a novel mechanism for tissue specific regulation of acyl‐ghrelin levels . In addition, although the role of the obestatin peptide remains unclear, it is distinct from acyl‐ghrelin in certain contexts.…”
Section: Calorie Restriction Regulates Brain Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, unacylated‐ghrelin does not share the protective effect of acyl‐ghrelin in a mouse model of PD . Intriguingly, the post‐translational acylation of ghrelin by the enzyme, ghrelin‐O‐acyl transferase, may provide a novel mechanism for tissue specific regulation of acyl‐ghrelin levels . In addition, although the role of the obestatin peptide remains unclear, it is distinct from acyl‐ghrelin in certain contexts.…”
Section: Calorie Restriction Regulates Brain Functionmentioning
confidence: 99%
“…113 Intriguingly, the post-translational acylation of ghrelin by the enzyme, ghrelin-O-acyl transferase, 114 may provide a novel mechanism for tissue specific regulation of acyl-ghrelin levels. 115 In addition, although the role of the obestatin peptide remains unclear, it is distinct from acyl-ghrelin in certain contexts. For example, obestatin has an opposing effect on ingestive behaviour 116 and does not modulate GH secretion.…”
Section: -Methyl-4-isoxazolepropionic Acid (Ampa) Receptors On Excitmentioning
confidence: 99%
“…This unique post-translational modification is catalyzed by the enzyme GOAT within the endoplasmic reticulum of ghrelin cells, and occurs before the peptide is processed by prohormone convertase 1/3, stored, and secreted [12, 14, 15]. It also has been claimed that ghrelin can undergo acylation after its secretion, within certain target tissues [16]. Binding of ghrelin to its only known receptor, GHSR, requires this acylation step.…”
Section: Biology Of the Ghrelin Systemmentioning
confidence: 99%
“…While this processing pathway for ghrelin maturation and acylation has been well established, a recent study suggests a potential new level of regulation within ghrelin signaling (Hopkins et al, 2017). Hopkins and co-workers demonstrated that both unacylated and acylated ghrelin promote bone marrow adipogenesis in mice in the presence of GOAT, with these effects absent in GOAT knockout mice.…”
Section: Discovery and Characterization Of Ghrelinmentioning
confidence: 99%